Improvement of Human Skin Cell Growth by Radiation-Induced Modifications of a Ge/Ch/Ha Scaffold - Enrione, J (SPRINGER, 2013)
Gelatin-/chitosan-/hyaluronan-based biomaterials are used in tissue engineering as cell scaffolds. Three gamma radiation doses (1, 10 and 25 kGy) were applied to scaffolds for sterilization. Microstructural changes of the irradiated polymers were evaluated by using scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). A dose of 25 kGy produced a rough microstructure with a reduction of the porosity (from 99 to 96 %) and pore size (from 160 to 123 ?m). Radiation also modified the glass transition temperature between 31.2 and 42.1 C (1 and 25 kGy respectively). Human skin cells cultivated on scaffolds irradiated with 10 and 25 kGy proliferated at 48 h and secreted transforming growth factor ?3 (TGF-?3). Doses of 0 kGy (non-irradiated) or 1 kGy did not stimulate TGF-?3 secretion or cell proliferation. The specific growth rate and lactate production increased proportionally to radiation dose. The use of an appropriate radiation dose improves the cell scaffold properties of biomaterials. © 2012 Springer-Verlag.